La Real Academia Sueca de Ciencias ha decidido entregar el Premio en Economía del Banco de Suecia en Memoria de Alfred Nobel, 1999! al Profesor Robert A. Mundell, Universidad de Columbia, Nueva York, E.E.U.U., por su análisis de política Monetaria y fisca - Sueca de Ciencias , Real Academia (2000)
Mundell's scientific contributions are very original. They soon transformed research into international macroeconomics. Characterized by a rare vision of the future development of international monetary agreements, they became increasingly relevant aspects in 2 discussion of monctarian and fiscal policy and exchange systems. The impact of Mundell's ideas was intensified by the simplicity and clarity of his exposition, whether in an algebraic or geometric form. His time at the International Monetary Fund (1961-1963) was an encouragement to investigate new problems and gave his research an additional influence among policy makers. This review was taken from official information from the Royal Swedish Academy of Sciences about the Award in Economics from the Bank of Sweden in Memory of Alfred Nobel, 1999, to Professor Robert A. Mundell. Columbia University, New York. USES. It has been published with the consent of Solgerd Bjorn-Rasmussen, Head of Information Department, The Royal Swedish Academy of Sciences.